From Iron Cage to Iron Shield? How Bureaucracy Enables Temporal Flexibility for Professional Service Workers - Briscoe, Forrest (Organization Science, 2007)
This paper develops a model of how organizations influence the temporal flexibility of professional service workers. The model starts by identifying a key source of temporal inflexibility for these workers: an inability to hand clients off among one other. Hand-offs are impeded by high levels of client-to-worker specificity, stemming from three common characteristics of professional service work. The organizational processes that reduce that specificity, and therefore facilitate hand-offs, function by (a) reshaping client participation and expectations about the nature of their service interactions, (b) partly standardizing client-related work practices, and (c) facilitating the sharing of knowledge about clients between workers. The presence of these organizational processes represents greater bureaucracy—an interesting twist, given that they create more temporal flexibility for workers. The model is grounded in field research conducted with primary care physicians, and is also evaluated using a unique survey data set of physician organizations. Implications are drawn for the study of temporal flexibility across professional services in general, as well as for recent attempts to rethink the meaning of bureaucracy for workers.